Changes of blood glucose and gastrointestinal hormones 4 months after Roux‐en‐Y gastric bypass surgery in Chinese obese type 2 diabetes patients with lower body mass index. Issue 2 (20th November 2012) - Wu, Qianlin; Xiao, Zhu; Cheng, Zhong; Tian, Haoming
Abstract Aims/Introduction The goal of this study was to evaluate the effect of Roux‐en‐Y gastric bypass (RYGB) on hyperglycemia and gastrointestinal hormones in Chinese obese type 2 diabetic patients with body mass index (BMI) between 28 and 35 kg/m2. Materials and Methods A total of eight obese type 2 diabetes patients with BMI 28–35 kg/m2 who underwent RYGB and 10 obese normal glucose tolerance (NGT) patients with no surgery were identified. BMI and blood glucose on baseline, and 2–4 months postoperative, changes of glucagon‐like peptide‐1 (GLP‐1), glucose‐dependent insulinotropic polypeptide (GIP), peptide YY (PYY), and oxyntomodulin (OXM) were recorded. Efficacy of RYGB was defined by the percentage of excess weight loss (%EWL) and amelioration of type 2 diabetes. Results The %EWL was 53.00 ± 26.25% in 2 month and 63.65 ± 33.71% in 4 month. Glycated hemoglobin changed from 7.2 ± 1.0% preoperative to 6.2 ± 0.9% in 2 month and 6.3 ± 1.2% in 4 month postoperative. The improvement rate of type 2 diabetes 4 months after RYGB was 83.3%. After surgery, area under the curve (AUC) GLP‐1 120 increased with no significance. AUC PYY 120 changed from 10.37 ± 5.45 pmol/L/min preoperative to 22.19 ± 10.61 pmol/L/min in 2 month and 22.04 ± 7.73 pmol/L/min in 4 month postoperative. Postoperative AUC OXM 120 was also higher than that of the preoperative level. AUC GIP 120 decreased from 13.06 ± 8.45 pg/mL/min preoperative to 8.71 ± 3.28 pg/ml/min in 2 month and 6.88 ± 2.33 pg/mL/min in 4 month postoperative. Conclusions Roux‐en‐Y gastric bypass has a beneficial effect on weight loss and glucose metabolism in obese type 2 diabetes patients with lower BMI. Postoperative concentrations of GLP‐1, PYY and OXM increased, whereas GIP decreased.